Design procedures for cold-formed stainless steel built-up columns assembled from equal-leg angles - Dobrić, J; Gluhović, N; Ivanović, J; Rossi, B (Elsevier, 2023)
In this paper, the structural behaviour of cold-formed stainless steel (CFSS) built-up T- and cruciform-section columns is studied experimentally and numerically, and the effect of discrete fasteners on their flexural and torsional rigidity is considered. To build the singly symmetrical built-up T-section columns, two equal-leg angle sections made of lean-duplex grade EN 1.4162 were assembled back-to-back. The doubly symmetrical built-up cruciform-section columns were composed of four star-oriented equal-leg angle sections made of austenitic grade EN 1.4301. They were connected using M8 bolts of class 8.8. Two pin-ended built-up T-section columns with length of 1000 mm, and four built-up cruciform-section columns with lengths of 600 mm and 2400 mm with semi-rigid support conditions, were tested under pure axial compression. As observed in the tests, built-up T-section columns experienced flexural-torsional buckling failure, whereas built-up cruciform-section columns failed in torsional buckling mode. Finite element models were validated against the conducted experiments and used to perform a parametric study of the structural behaviour of CFSS built-up T- and cruciform-section columns. The study included the column length, cross-sectional dimensions and bolt spacing as variables. The experimental and numerical data, i.e., the column strengths and failure modes, were compared against the results obtained based on the European and North American Specifications alongside a recent method established for cold-formed carbon steel equivalents and based on the Direct Strength Method (DSM). It is shown that the DSM-based approach predicts the ultimate buckling resistances of the considered built-up columns more accurately than the available codified design methods.